SCIENTIFIC, ARTISTIC AND SOCIAL ASPECTS OF THE CONCEPTUALIZATION OF SPACE IN THE ENLIGHTENMENT - Marina A. Vasilyeva (Russian Studies in Culture and Society)
The article is devoted to the study of the conceptualization of space in the Enlightenment. The author examines the scientific approach to space that developed in the New Age, the artistic understanding of space and the practices of vision that manifest themselves in painting, as well as a new assessment of the social significance of space and the emergence of the idea of public spaces. The article examines the general ideological foundations of the Enlightenment that influenced the new attitude to space and its social role. In particular, an assumption is made about the high significance of ancient images in the process of forming a single language and a common space of communication for different intellectual circles of the 18th century. The article examines the main positions that are important for the concept of “environmental design” that developed at that time: an instrumental attitude to space and the deliberate variability of forms, the projectivity of the environment, as well as the presence of social groups that have access to this design. The author suggests considering the Enlightenment (the 18th century and the first half of the 19th century) as the beginning of a great deal of work on creating effective methods and techniques for creating spaces in which social and political goals were realized through aesthetic techniques.